Pencegahan stunting balita melalui refreshing kader Posyandu dengan pelatihan pemantauan pertumbuhan dan pengisian KMS - Febry, Fatmalina; Misnaniarti, Misnaniarti; Ainy, Asmaripa; Budi, Iwan Stia; Safriantini, Dian (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2022)
Stunting is a chronic nutritional problem caused by multiple factors and is intergenerational. The incidence of stunting shows the problem of chronic malnutrition and occurs at the age of toddlers. Monitoring the growth of children under five is very important to detect growth faltering at an early stage. To determine this growth, weighing toddlers every month is very necessary. Anthropometric measurements are usually carried out by cadres at the Posyandu. However, the cadres cannot monitor the growth of toddlers either through anthropometric measurements (weight and height) or by filling out the KMS. This is because most of the cadres have never received training on anthropometric measurements and filling in the KMS. The results of this activity showed that most of the cadres experienced an increase in scores before and after the training, namely an increase in nutritional knowledge (54.3%), anthropometric measurements (78.2%), and KMS filling (58.7%). Based on the results of the Wilcoxon test showing a p value of 0.000 < 0.005, there is a difference in knowledge scores before and after the intervention, both knowledge of nutrition, anthropometric measurements of toddlers and filling KMS increases. It can be concluded that this cadre training activity was quite successful, seen from the results of the frequency distribution obtained and the results of statistical tests. It is necessary to carry out regular training related to monitoring the growth and reading of KMS, especially if there is a change of cadres.